KAPABILITAS PUSPENERBAL DALAM MELAKSANAKAN EVAKUASI MEDIS UDARA DI MASA PANDEMI COVID-19 GUNA MENDUKUNG KEAMANAN NASIONAL - Dyah Vinianti (Jurnal Manajemen Bencana (JMB), 2023)
The capability of Puspenerbal is needed for carrying out air medical evacuation during the Covid-19 pandemic. This study aims to analyze Puspenerbal's ability to carry out air medical evacuation during the Covid-19 pandemic, obstacles faced by Puspenerbal in carrying out air medical evacuation during the Covid-19 pandemic, and capacity building for Puspenerbal in carrying out air medical evacuation during the Covid-19 pandemic. This research uses qualitative descriptive methods through secondary data collection, documents and literature studies. The study's findings revealed that Puspenerbal can fulfill requests for air medical evacuation with several limitations, Puspenerbal faced obstacles in carrying out air medical evacuation during the Covid-19 pandemic as a result of risk factors in its implementation, and Puspenerbal's capability in carrying out air medical evacuation during the Covid-19 pandemic must be increased. The conclusion from this study is that the limitations and obstacles that arise in the implementation of air medical evacuation require Puspenerbal to increase its capabilities by preparing short, medium, and long-term plans to support the implementation of air medical evacuation. It is hoped that the increased capability and experience gained during the Covid-19 pandemic will become the basis and guidelines for implementing air medical evacuation during non-pandemic times or during other infectious disease pandemics to support national security.